2016
DOI: 10.1371/journal.pone.0149976
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Reveals the Alteration of the Expression of Novel Genes in Ethanol-Treated Embryoid Bodies

Abstract: Fetal alcohol spectrum disorder is a collective term representing fetal abnormalities associated with maternal alcohol consumption. Prenatal alcohol exposure and related anomalies are well characterized, but the molecular mechanism behind this phenomenon is not well characterized. In this present study, our aim is to profile important genes that regulate cellular development during fetal development. Human embryonic carcinoma cells (NCCIT) are cultured to form embryoid bodies and then treated in the presence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…A similar result was previously reported in miR‐9‐2/3 knockout mice, which exhibit fetal growth retardation, microencephaly, and other features that are also common to fetal alcohol spectrum disorder (FASD) (Shibata, Nakao, Kiyonari, Abe, & Aizawa, ). Mandal and his colleagues cultured embryoid bodies exposed to ethanol for 3 and 7 days to profile transcriptomic expressions during early development (Mandal, Halder, et al, ; Mandal, Kim, et al, ). Transcriptomic analysis showed that ethanol dysregulated the expression of the MIR663 and MIRLET7DHG genes after 3 days of ethanol exposure (Mandal, Kim, et al, ).…”
Section: Alcohol‐mediated Alteration Of Mirna Expression In the Develmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar result was previously reported in miR‐9‐2/3 knockout mice, which exhibit fetal growth retardation, microencephaly, and other features that are also common to fetal alcohol spectrum disorder (FASD) (Shibata, Nakao, Kiyonari, Abe, & Aizawa, ). Mandal and his colleagues cultured embryoid bodies exposed to ethanol for 3 and 7 days to profile transcriptomic expressions during early development (Mandal, Halder, et al, ; Mandal, Kim, et al, ). Transcriptomic analysis showed that ethanol dysregulated the expression of the MIR663 and MIRLET7DHG genes after 3 days of ethanol exposure (Mandal, Kim, et al, ).…”
Section: Alcohol‐mediated Alteration Of Mirna Expression In the Develmentioning
confidence: 99%
“…Mandal and his colleagues cultured embryoid bodies exposed to ethanol for 3 and 7 days to profile transcriptomic expressions during early development (Mandal, Halder, et al, 2016;Mandal, Kim, et al, 2016). Transcriptomic analysis showed that ethanol dysregulated the expression of the MIR663 and MIRLET7DHG genes after 3 days of ethanol exposure (Mandal, Kim, et al, 2016). Microarray analysis of differentially expressed genes after 7 days of ethanol exposure showed altered expression levels of the MIR9-3, MIR15B, MIR186, MIR19B2, MIR301A, MIR302A, MIR302B and MIRLET7F1 genes (Mandal, Halder, et al, 2016).…”
Section: Alcohol-mediated Alteration Of Mirna Expression In the Devmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol is well known as a teratogenic agent that affects the normal development of a developing embryo. Fetal alcohol spectrum disorder (FASD) is the term commonly used to denote alcohol-related neonatal abnormalities [ 1 , 2 ]. The most severe form of FASD is known as fetal alcohol syndrome (FAS), and manifests as growth retardation, facial abnormalities, and central nervous system (CNS) deficiencies [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have described genetic susceptibilities to alcohol-mediated defects. Microarray analysis and next-generation sequencing techniques have found that many developmental genes are altered by in utero alcohol exposure [ 1 , 2 , 3 , 4 , 7 , 8 , 9 , 10 ]. However, the underlying causes of these alcohol-mediated disorders remain unclear.…”
Section: Introductionmentioning
confidence: 99%